2007
DOI: 10.1111/j.1468-2435.2007.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Pro‐Regularization Movements in Western Europe

Abstract: Contrary to the image conveyed by existing research on irregular migrants as powerless and exploited victims of restrictive immigration policies, irregular migrants in some European countries display a strong potential for collective action. In France, Spain and Switzerland since the mid-1990s pro-regularization movements have emerged which have claimed the collective regularization of illegal migrants. At the centre of these new social movements were illegal migrants from sub-saharan Africa, Latin America and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 19 publications
1
40
0
2
Order By: Relevance
“…They would in other words confine themselves to the private arena, attend to the satisfaction of their basic physical needs, and avoid the public sphere where free and equal citizens debate the direction of the nation. However, contrary to expectations, recent studies have shown that undocumented immigrants have done the opposite in countries as diverse as the United States, France, Germany, Great Britain, and the Netherlands (Anderson, 2010;Barron et al, 2011;Cisse´, 1999;Iskander, 2007;Laubenthal, 2007;Nicholls, 2011;Sime´ant, 1998;Voss and Bloemraad, 2011). In spite of differences in the politics and cultures of these countries, some undocumented immigrants have not only resisted being relegated to the margins of national citizenship but have taken an active role in engaging in public debates over citizenship, rights, and nationhood.…”
Section: Introductionmentioning
confidence: 94%
“…They would in other words confine themselves to the private arena, attend to the satisfaction of their basic physical needs, and avoid the public sphere where free and equal citizens debate the direction of the nation. However, contrary to expectations, recent studies have shown that undocumented immigrants have done the opposite in countries as diverse as the United States, France, Germany, Great Britain, and the Netherlands (Anderson, 2010;Barron et al, 2011;Cisse´, 1999;Iskander, 2007;Laubenthal, 2007;Nicholls, 2011;Sime´ant, 1998;Voss and Bloemraad, 2011). In spite of differences in the politics and cultures of these countries, some undocumented immigrants have not only resisted being relegated to the margins of national citizenship but have taken an active role in engaging in public debates over citizenship, rights, and nationhood.…”
Section: Introductionmentioning
confidence: 94%
“…En este sentido, podemos dar cuenta de la emergencia de una conciencia colectiva y simultánea entre los distintos movimientos de inmigrantes sin-papeles que está teniendo lugar tanto en el contexto europeo como en el americano (Aierbe 2000;Cissé 2000;Coutin 2000;Krueger 2001;Laubenthal 2007;Nyers 2008;Suarez et al 2008). Dadas las circunstancias de control y persecución de la inmigración, la obtención de los permisos se había convertido en una cuestión vital para muchas personas.…”
Section: Los Sin-papeles Como Sujetos De Juridicidadunclassified
“…Immigrants' political action is seldom enacted in isolation. As Laubenthal (2007) argues, immigrants' movements count on the support of other more secure actors: citizens, NGOs, trade unions, religious groups and so on. Equally, protest and campaigning against deportation and removal is not just in the hands of removable migrants themselves.…”
Section: Migrants and Political Agencymentioning
confidence: 99%